Effects of hot water dip treatment on physicochemical characteristics, anthracnose (Colletotrichum musae) control and enzymatic activity of berangan banana (Musa sapientum L.) during ripening - Mirshekari, Amin (2012)
Banana, as an important export fruit, is a highly perishable commodity.Postharvest rot is the major factor limiting the extension of storage life of banana. The beneficial effect of heat treatment to control decay and prolong the shelf life has been reported on various fruits. To achieve the best combination of water temperature and dipping time, Berangan banana fruit was treated with water at 25 (control), 45, 50 and 55 ºC for 10, 20 and 30 min. The results obtained in the first experiment showed that fruit firmness, peel and pulp colour (hº) increased significantly, while respiration rate, ethylene production, peel and pulp colour (L* and C*), soluble solids concentration (SSC), titratable acidity (TA) and pH decreased significantly when hot water temperature and dipping time increased. Hot water of 45 ºC for 10 and 20 min dipping time did not show any significant difference in fruit quality as compared to control. Hot water dip treatment of 45 ºC for 30 and 55 ºC for 10 min retarded some of fruit ripening processes in Berangan banana. The low respiration rate, ethylene production, peel and pulp colour (L*, C* and hº), SSC, TA and pH, and high firmness in Berangan banana treated with hot water of 50 ºC for 10 and 20 min indicated that this combination treatment could delay fruit ripening. Fruit dipped in hot water of 50 ºC for 30 min and 55 ºC for 20 and 30 min illustrated slight to severe peel blackening and suppressed ripening process in Berangan banana. For anthracnose control, fruit was treated with hot water at 50 ºC for 0, 10 and 20 min without or with fungicide. The results clearly demonstrated that hot water without or with fungicide reduced severity of anthracnose in inoculated Berangan banana. Spore germination of Colletotrichum musae was suppressed completely with hot water of 50 ºC in 10 and 20 min without or with fungicide. Anthracnose symptoms did not develop in fruits dipped with hot water at 50 ºC for 20 min either with or without fungicide during 7 days of ripening. The results of enzymatic activity experiment indicated that hot water dip at 50 ºC for 10 and 20 min could decrease cell wall degrading enzymes activity such as polygalacturonase (PG), pectin methylesterase (PME) and pectate lyase (PL) of Berangan banana fruit. The scanning electron microscope (SEM) micrographs showed that hot water dip at 50 ºC for 10 and 20 min could melt the fruit epicuticular waxes, so that it covered and sealed the microscopic cracks on the fruit surface. The results of ultrastructural investigation indicated that hot water of 50 ºC for 20 min has lesser loss of cell rigidity and dissolution of cell wall pectin fractions of tissues in Berangan banana. It can be concluded that hot water dip treatment using 50 ºC for 10 min showed reasonable delay of fruit ripening and anthracnose control as compared to other combination of temperature and dipping time. This combination of temperature and dipping time could be the most possible to be used as a commercial treatment in extending the shelf life of Berangan banana for local consumption and export purposes.